Morphodynamics of submarine channel inception revealed by new experimental approach - Jan de Leeuw (Nature Portfolio, 2016)
Suspended sediment currents travel through channels on the ocean floor to deliver enormous volumes of sediment to the deep ocean. Here, using a new approach for scaled laboratory experiments, the authors show how feedback between these currents and their deposits drive the formation of these submarine channels.